Growth Pattern of Skipjack Tuna (Katsuwonus Pelamis) Landed in PPI Kedonganan Bali - I Gusti Ayu Febiana Putri Wardeni; Pande Gde Sasmita Julyantoro; Rani Ekawaty (Fakultas Kelautan dan Perikanan Universitas Udayana, 2019)
Skipjack Tuna (Katsuwonus Pelamis) is one of the big pelagic fish in fishery resources that has high economic value and plays an important role in export activity in Indonesia. Catch activities for consumption needs for people could threatened of Skipjack Tuna availability. The growth pattern of Skipjack Tuna is needed to used as references for the appropriate management plan to protect Skipjack Tuna. The research was conducted from February to April 2017 at PPI Kedonganan, Kuta District, Badung, Bali. The fish were collected by simple random sampling method. This study showed that gillnet and handline were used as fishing gears. The length frequency distributions were in the long-range of 315-337 mm means the catch fish is still young. The growth pattern of Skipjack Tuna was negative allometric means length growth was faster than weight growth. The growth parameters of Skipjack Tuna were obtained by the asymptotic length (Linf) of 875.2 mm, growth coefficient (K) of 0.09, and theoretical age (t0) of -0.78. Skipjack Tuna have small body size with condition factors were ranged from 0.8783-1.7269. It can be concluded that these methods can be used to determine the appropriate management efforts.